The Predictive Value of Radiostereometric Analysis for Stem Survival in Total Hip Arthroplasty. A Systematic Review. Issue 3 (May 2014) - de Vries, Lieke M.A.; van der Weegen, Walter; Pilot, Peter; Stolarczyk, Piotr A.; Sijbesma, Thea; Hoffman, Erik L.
Background: The high precision of radiostereometric analysis (RSA) has enabled us to predict long-term implant survival with a small sample of patients followed for a relatively short period of time. The purpose of our systematic review was to validate the predictive value of two-year RSA results on long-term survival of different types of primary total hip arthroplasty stems. Methods: We systematically reviewed literature to determine the maximum total point motion (MTPM), distal migration and rotation of stem designs and correlated these values to survival rates for aseptic loosening of these specific stems in arthroplasty registries. Results: We included 32 studies describing migration of 15 different stem designs. The mean MTPM for straight polished cemented stems was 1.35 mm, for other cemented stems 0.83 mm and for other uncemented stems 1.50 mm. No data were available for the uncemented collared stem. Mean distal migration for straight polished cemented stems was 1.24 mm, for other cemented stems 0.26 mm, the uncemented collared stem 0.40 mm and for other uncemented stems 0.66 mm. Internal rotation was presented for 13 stems and all stems rotated into retroversion. All stems showed 10-year survival rates of >97% corrected for aseptic loosening. Discussion: Reporting RSA results in a universal way including interpretation of outliers could improve the predictive value of RSA, allowing this technique to be an important tool during the phased introduction of new implant designs. However, a quality assessment of the data by an experienced reviewer is essential.